Communication System in Niklas Luhmann’s Perspective: Conceptual Relevance in the Digital Era - Taufik (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This study examines communication systems from the perspective of Niklas Luhmann’s social systems theory, focusing on their relevance in the digital era. Luhmann views communication not as an individual act, but as a fundamental element that shapes and reproduces social systems autopoietic. This approach allows for an in-depth analysis of the dynamics of digital communication, which is complex, differentiated, and operates in a closed manner, yet is interconnected with other systems through structural coupling. The research method used is a literature review of Luhmann’s main works and a conceptual analysis of contemporary digital communication phenomena. The results show that digital communication systems have their own operational logic constructed by internal codes and structures, such as in the case of social media algorithms, virality, and mediation between legal, political, and economic systems. Luhmann’s theory proves relevant as a conceptual framework for understanding how communication in the digital era is no longer neutral, but rather shapes social reality through a systemic and autonomous reproductive process.